Computational models of subjective feelings in psychiatry. (February 2023) - Kao, Chang-Hao; Feng, Gloria W.; Hur, Jihyun K.; Jarvis, Huw; Rutledge, Robb B.
Abstract: Research in computational psychiatry is dominated by models of behavior. Subjective experience during behavioral tasks is not well understood, even though it should be relevant to understanding the symptoms of psychiatric disorders. Here, we bridge this gap and review recent progress in computational models for subjective feelings. For example, happiness reflects not how well people are doing, but whether they are doing better than expected. This dependence on recent reward prediction errors is intact in major depression, although depressive symptoms lower happiness during tasks. Uncertainty predicts subjective feelings of stress in volatile environments. Social prediction errors influence feelings of self-worth more in individuals with low self-esteem despite a reduced willingness to change beliefs due to social feedback. Measuring affective state during behavioral tasks provides a tool for understanding psychiatric symptoms that can be dissociable from behavior. When smartphone tasks are collected longitudinally, subjective feelings provide a potential means to bridge the gap between lab-based behavioral tasks and real-life behavior, emotion, and psychiatric symptoms. Highlights: Models of subjective feelings can quantify the influence of many factors. Subjective feelings can be dissociable from behavior in psychiatric disorders. Smartphones can be used to measure subjective feelings in tasks and real life.